1990
DOI: 10.1111/j.1440-169x.1990.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Statocyte and Ocellar Pigment Cell in Embryos and Larvae of the Ascidian, Styela plicata (Lesueur)

Abstract: The processes of formation of two pigmented cells, the statocyte and the ocellar pigment cell, in the cerebral vesicle of larvae of the ascidian Sfyela plicata were investigated in whole mount specimens and serial paraffin sections by light microscopy. The pigmentations of the two cells became visible simultaneously in embryos at the stage of tail elongation, 5-6 hr after fertilization. The pigmented cells were at first located side by side in the dorsal wall of the neurocoel. Growth of the pigment mass in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Figure 6C,D shows the SEM images of the inner region of the brain vesicle. Small vesicular structures protrude from the wall and are located near coronet cells, which are also spherical and presumed to constitute a pressure organ (Eakin and Kuda,1971; Katz,1983; Ohtsuki,1990). The size of this small spherical structure is ≈0.6–0.8 μm in diameter, while that of the coronet cell is ≈2 μm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6C,D shows the SEM images of the inner region of the brain vesicle. Small vesicular structures protrude from the wall and are located near coronet cells, which are also spherical and presumed to constitute a pressure organ (Eakin and Kuda,1971; Katz,1983; Ohtsuki,1990). The size of this small spherical structure is ≈0.6–0.8 μm in diameter, while that of the coronet cell is ≈2 μm.…”
Section: Resultsmentioning
confidence: 99%
“…The dehydrated larvae were cryofractured at liquid nitrogen temperature. The larvae, cut through their brain vesicle, were rinsed, dried, and coated with a thin layer of Pt‐Pd, as described previously (Ohtsuki,1990). All dried and coated materials were examined by scanning electron microscopy (Hitachi S‐800, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Electron microscopic observation showed that the otolith is a spherical mass of pigment granules connected to the midline of the floor of SV by a narrow stalk (Dilly 1961, 1964; Eakin and Kuda 1971; Ohtsuki 1990; Sakurai et al . 2004).…”
Section: Structural Organization Of Nervous Systemmentioning
confidence: 99%
“…The pigmented sensory organ located anterior is an otolith, used for the perception of gravity, and the posterior one is an ocellus, used for light reception (Tsuda et al 2003b;Sakurai et al 2004). Electron microscopic observation showed that the otolith is a spherical mass of pigment granules connected to the midline of the floor of SV by a narrow stalk (Dilly 1961(Dilly , 1964Eakin and Kuda 1971;Ohtsuki 1990;Sakurai et al 2004). The otolith-associated neurons extend their axon to the PB (Horie et al 2008a).…”
Section: Structural Organization Of Nervous Systemmentioning
confidence: 99%
“…In particular, the larvae of the styelids have either simplified ocelli, as in Styela partita ( Grave 1944), or compound sensory structures, as in the photolith of the Botryllinae ( Garstang and Garstang 1928; Grave, 1934; Grave and Riley 1935; Torrence and Cloney 1988). The solitary Styela plicata ( Torrence 1983; Ohtsuki 1990a,b) and Cnemidocarpa finmarkiensis ( Vorontsova and Malakhov 1984) possess only a rudimentary ocellus and a photolith. Other species have a statocyst but no pigmented ocellus, e.g.…”
Section: Discussionmentioning
confidence: 99%